1996
DOI: 10.1051/lait:19961-29
|View full text |Cite
|
Sign up to set email alerts
|

Les autolysines des bactéries lactiques

Abstract: Résumé -Les autolysines sont définies comme des enzymes bactériennes endogènes capables d'hydrolyser le peptidoglycane, qui est le constituant majeur et essentiel de la paroi. Leur action peut donc induire la lyse bactérienne. Un certain nombre d'autolysines ont été caractérisées au niveau moléculaire chez différentes bactéries. Le rôle physiologique de ces enzymes, potentiellement dangereuses pour la cellule, n'est pas complètement élucidé. Elles jouent un rôle dans la séparation des cellules en fin de divisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 19 publications
2
27
1
Order By: Relevance
“…However, concurring with previous publications, the thermophilic bacteria generally disappeared in a brief time (1-3 months), thus releasing a wealth of enzymes [3,7,8,17,31]. An undoubtedly important contribution was made by the mesophilic lactic acid bacteria (essentially L. casei, L. paracasei, L. rhamnosus, pediococci) which presented meaningful counts in the fifth month of ageing, thereby showing a significantly higher level compared to what has been reported thus far in literature with specific reference to Grana Padano [1].…”
Section: Discussionsupporting
confidence: 91%
“…However, concurring with previous publications, the thermophilic bacteria generally disappeared in a brief time (1-3 months), thus releasing a wealth of enzymes [3,7,8,17,31]. An undoubtedly important contribution was made by the mesophilic lactic acid bacteria (essentially L. casei, L. paracasei, L. rhamnosus, pediococci) which presented meaningful counts in the fifth month of ageing, thereby showing a significantly higher level compared to what has been reported thus far in literature with specific reference to Grana Padano [1].…”
Section: Discussionsupporting
confidence: 91%
“…A similar situation occurs in S. aureus, in which most of the multiple bands detected by renaturing SDS-PAGE result from the processing of the major autolysin Atl (Foster, 1995). In agreement with previous reports (Ostlie et al, 1995b;Chapot-Chartier 1996;Lortal et al, 1997), this study revealed that the peptidoglycan hydrolase profile of strains within a species is conserved.…”
Section: Discussionsupporting
confidence: 91%
“…The highest levels of proteolysis observed in Teleme cheeses made with the thermophilic culture, regardless of the type of milk used, could be due to an earlier lysis of thermophilic starter bacteria that could have enhanced the early release of intracellular enzymes into the cheese matrix and could have increased the rate of proteolysis [6]. The overall proteolytic activity of lactobacilli has been found to be higher than that of Lc.…”
Section: Effect Of Type Of Culturementioning
confidence: 90%